JURIDICAL REVIEW OF THE PROTECTION OF THE RIGHTS OF CONCURRENT CREDITORS IN THE OCCURRENCE OF BANKRUPTCY OF COOPERATIVE LEGAL ENTITIES - Jodan Juliano (Jurnal Scientia, 2023)
In its implementation, cooperatives still maintain business units that tend to cause losses, so to cover these losses cooperatives use capital from loans from banking institutions, non-banks and cooperative members. The loan capital gives rise to the rights and obligations for the cooperative to return the principal and interest from the loan capital. If the cooperative cannot repay it creates debt for the cooperative and the cooperative can be filed for bankruptcy by its creditors. In writing this law there are 2 (two) problems discussed, namely how The position of cooperative members in the occurrence of bankruptcy in cooperative legal entities is reviewed from Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU) and what are the legal consequences for cooperatives that are declared bankrupt by the Court. The research method used is the juridical-normative method using the library method, namely the sources of applicable laws and regulations, books, journals, magazines and the internet. The position of cooperative members in the occurrence of bankruptcy in cooperative legal entities in terms of Law Number 37 of 2004 concerning Bankruptcy and PKPU is as concurrent creditors because cooperative members still have receivables in the form of principal savings and mandatory savings in the cooperative. Cooperative members will receive a distribution if all the obligations of the cooperative to all creditors have been fulfilled. Cooperative members are creditors who are included in the concurrent creditors who get the last share of the bankruptcy estate. The members of the cooperative in getting the distribution of the remaining bankrupt assets only wait for the remaining bankrupt assets. The legal consequence of a cooperative that is declared bankrupt is that all assets of the Debtor at the time of the bankruptcy declaration decision are made and everything obtained during the bankruptcy and the cooperative loses the right to manage and control their assets from the day the judge declares bankruptcy, because it is related to the management and control of their assets. the settlement of the cooperative's assets is transferred to the curator.